PELAKSANAAN RESTORATIVE JUSTICE TERHADAP ANAK PELAKU TINDAK PIDANA LALU LINTAS (Studi Pelaksanaan Restorative justice di Polres Kudus) - Istanto, Yusuf (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
This study aims to Know the Implementation of Restorative Justice Against Children Traffickers by Traffic Unit Traffic Police Kudus Traffic. The research method used in this research is empirical juridical method. Specification of research that writer use that is descriptive qualitative. Data collection techniques were conducted with in-depth interviews to the parties involved in research, direct observation, and document recording. Based on the results of the research analysis, it can be seen that the implementation of Restorative Justice on the children of the perpetrators of the criminal acts of traffic by the investigators of Laka Luas unit of the Kudus Police is conducted based on the provisions of Article 5, Article 6, Article 7 and Article 8 of the Criminal Justice System Law and the Joint Decision of the Chairman Supreme Court, Attorney General, Chief of Police of the Republic of Indonesia, Minister of Law and Human Rights, Minister of Social Affairs, and Minister of State for the Protection of Women and Children on Handling Children Against the Law. The process of restorative justice in criminal cases of traffic accidents conducted by the AP is conducted through consultation with the involvement of children and parents, victims, social guidance, based on the approach of Restorative Justice (Article 8 paragraph (1)). Restorative justice is a process of restorative justice by involving all relevant parties. The law on the criminal justice system prioritizes the consent of the victim and / or his family to restorative justice.